(untitled) (Szociológiai Szemle, 2024)
In the framework of the International Social Science Project a cross-national survey was carried out in 1996 on representative samples of 23 countries of the world. The participating coutries represent East European, West European countries as well the US, Australia, New Zealand, Japan and Philippines. Multivariate analyses of the data showed that the present-day empirical patterns of national identification do not correspond with historical types of national formation. In order to reveal specific effects of class, age, and gender on national identification further analyses are needed.